Improvement of performance through learning motivation on accuracy of forehand service in badminton among students - Siti Nurhaliza; Ridho Bahtra; Tjung Hauw Sin; Ahmad Chaeroni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to examine the direct and indirect effects of arm muscle strength, eye-hand coordination, and learning motivation on forehand service accuracy in badminton among junior high school students. A quantitative approach with path analysis was used. The sample consisted of 49 male students selected through random sampling. Data were collected using a push-up test for arm muscle strength, a tennis ball throw-and-catch test for eye-hand coordination, a 50-item Likert-scale questionnaire for learning motivation, and a modified forehand service accuracy test. The findings revealed that arm muscle strength (0.393), eye-hand coordination (0.337), and learning motivation (0.278) had significant direct effects on forehand service accuracy. Additionally, arm muscle strength and eye-hand coordination showed indirect effects through learning motivation, contributing 5.2% and 3.7%, respectively. Both physical and psychological factors significantly influence forehand service accuracy. Integrating physical training and motivational strategies is essential to enhance badminton performance.